Vibrational and nonlinear optical properties of amine-capped push-pull polyynes by infrared and Raman spectroscopy. (October 2021) - Marabotti, Pietro; Milani, Alberto; Lucotti, Andrea; Brambilla, Luigi; Tommasini, Matteo; Castiglioni, Chiara; Męcik, Patrycja; Pigulski, Bartłomiej; Szafert, Sławomir; Casari, Carlo Spartaco
Abstract: The vibrational properties of a series of push-pull polyynes have been studied by infrared and Raman spectroscopy. The simultaneous activation of a strong infrared and Raman mode, i.e. the collective vibration of CC bonds of the sp carbon chain, highlights the effectiveness of a polyyne bridge in promoting charge transfer between the electron donor (D) and acceptor (A) ends, thus suggesting that ad-hoc functionalized polyynes are worth being explored as building blocks of organic materials with attractive first-order optical nonlinearity. The optical, electronic, and vibrational properties of these molecules have been investigated with the support of density functional theory calculations, as well as the electronic and vibrational first hyperpolarizabilities (β). The mid-low region of the IR spectra (800-1600 cm −1 ) has been analyzed in detail, searching for marker bands of the specific terminations of the different sp carbon chains thus achieving a complete vibrational characterization of sp hybridized push-pull systems.